Callicarpa bachmaensis Soejima & Tagane (Lamiaceae), a new species from Bach Ma National Park in Thua Thien Hue Province, Central Vietnam - Soejima, Akiko (2023)
A new species, Callicarpa bachmaensis Soejima & Tagane, sp. nov., is described and illustrated from Bach Ma National Park in Thua Thien Hue Province, Central Vietnam. This species has a characteristic liana habit, white corolla, and narrowly elliptic to narrowly lanceolate, entire, occasionally subequal leaves, by which it is clearly distinguished from the other previously known species of this genus.